2018
DOI: 10.3390/molecules23030609
|View full text |Cite
|
Sign up to set email alerts
|

First Look at the Venom of Naja ashei

Abstract: Naja ashei is an African spitting cobra species closely related to N. mossambica and N. nigricollis. It is known that the venom of N. ashei, like that of other African spitting cobras, mainly has cytotoxic effects, however data about its specific protein composition are not yet available. Thus, an attempt was made to determine the venom proteome of N. ashei with the use of 2-D electrophoresis and MALDI ToF/ToF (Matrix-Assisted Laser Desorption/Ionization Time of Flight) mass spectrometry techniques. Our invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 50 publications
3
46
0
Order By: Relevance
“…According to the latest data concerning Naja ashei, its venom is composed mostly of 3FTxs (69%) and PLA 2 s (27%). However, there are also small amounts of SVMPs (2.1%), VNGF (1%), CRISPs (0.7%), CVF (0.12%), and 5 -nucleotidases (0.014%) [19]. After fractionation, we were able to discover other groups of low abundant proteins that were previously described in other snake species, for example, L-amino acid oxidases or snake venom serine proteases (SVSPs) ( Table 1).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…According to the latest data concerning Naja ashei, its venom is composed mostly of 3FTxs (69%) and PLA 2 s (27%). However, there are also small amounts of SVMPs (2.1%), VNGF (1%), CRISPs (0.7%), CVF (0.12%), and 5 -nucleotidases (0.014%) [19]. After fractionation, we were able to discover other groups of low abundant proteins that were previously described in other snake species, for example, L-amino acid oxidases or snake venom serine proteases (SVSPs) ( Table 1).…”
Section: Discussionmentioning
confidence: 70%
“…However, the group that was widely described in terms of its antibacterial properties is LAAOs. Interestingly, this group of proteins was not detected during our previous analysis of the Naja ashei venom proteome [19]. This may indicate that the share of this group in the whole venom is negligible, but fractionation caused a significant reduction of the sample complexity, thus allowing for the identification of low abundant proteins.…”
Section: Discussionmentioning
confidence: 81%
“…In the 2-D Quant Kit method, copper ions attach to the peptide bonds in the protein, so this method is independent of the amino acid composition of the proteins in the sample. This kit has been repeatedly used to measure the concentration of proteins in venom [28,39] and this is also the most commonly used method in our laboratory [10,34,35,40]. However, obtained results by 2-D Quant Kit and Bradford for A. contortrix venom show low variability, whereas for N. ashei venom, the differences are large.…”
Section: Discussionmentioning
confidence: 99%
“…L-amino acid oxidases, CRISP proteins and lectin-like proteins are less abundant/less often seen [34,50]. On the other hand, 70% of N. ashei venom is composed of 3FTx proteins, less than 30% are PLA 2 and about 2% SVMP, and the remaining groups-CRISP, VNGF (Venom Nerve Growth Factor), nucleases and CVF (Cobra Venom Factor)-occur in trace amounts [35]. Subsequent studies on fractions obtained from chromatographic separation of this venom have shown that LAAO, SVSP and other proteins are also present, but they represent a very small percentage of venom proteins [51].…”
Section: Discussionmentioning
confidence: 99%
“…African spitting cobras are associated with morbidity and mortality in sub-Saharan Africa [3][4][5][6][7][8][9][10][11]. Toxicological/pathological effects include blistering, edema, necrosis, respiratory paralysis and ophthalmia [8][9][10][11][12][13]. Naja ashei is one of the African spitting cobras and is a category 1 snake in Kenya, Ethiopia, Somalia, Uganda, and a category 2 snake in Tanzania [14].…”
Section: Introductionmentioning
confidence: 99%